《川崎病心血管后遗症的诊断和管理指南(JCS/JSCS 2020)》解读 (Zhongguo Dang Dai Er Ke Za Zhi, 2021)
Kawasaki disease is the main cause of acquired heart disease in children. The cardiovascular sequelae of Kawasaki disease, such as coronary artery lesion and giant coronary aneurysm, have a great impact on children's physical and mental health. The Japanese Circulatory Society and the Japanese Society of Cardiac Surgery jointly released the JCS/JSCS 2020 guideline on diagnosis and management of cardiovascular sequelae in Kawasaki disease in July, 2020, which systematically introduces the advances in the diagnosis and management of cardiovascular sequelae of Kawasaki disease. The article gives an interpretation in the severity evaluation of Kawasaki disease and diagnosis, treatment and long-term management of cardiovascular sequelae in the guideline.